Valoración del impacto social de la atención odontológica brindada por los estudiantes de la carrera de Odontología en el barrio Motupe en el periodo marzo-julio 2015 - Roldán Íñiguez, Andrea Cecibel (2015)
The purpose of this research was to assess the social impact of the odontology attention given by the students of Odontology in Motupe neighborhood during the period march-july 2015; the impact was evaluated by the percentage differences of oral health indicators before and after the odontology action, in which the population was represented by 7593 individuals of Motupe neighborhood and the established sample was 365 individuals. The recollecting technique was the direct observation and the instruments: generating questions, questionnaire,and observation sheets. The impact was evaluated by means of motivation, satisfaction, and participation, reflected on the community when the odontology action finished; in order to carry out the evaluation, techniques were as the recollecting technique and as instrument the questionnaire of closed questions. The results evidenced that 73,70 % received the benefits from the Pediatric Dentistry Clinic of the University Hospital of Motupe, this shows that although the community tends to participate passively, it feels satisfied with the service provided by the students. Key words: social impact, odontology attention, post dental surgical treatment satisfaction